2022
DOI: 10.4103/uros.uros_31_22
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge and Novel Frontiers in Lower Urinary Tract Dysfunction after Spinal Cord Injury

Abstract: This review article aims to summarize the recent advancement in basic research on lower urinary tract dysfunction (LUTD) following spinal cord injury (SCI) above the sacral level. We particularly focused on the neurophysiologic mechanisms controlling the lower urinary tract (LUT) function and the SCI-induced changes in micturition control in animal models of SCI. The LUT has two main functions, the storage and voiding of urine, that are regulated by a complex neural control system. This neural system coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 119 publications
2
22
0
Order By: Relevance
“…While it is difficult to grasp and integrate the enormous number of published results, it is clear that NDO pathophysiology is complex and, consequently, its treatment and management is difficult. Like other researchers [ 18 ] and following the present review, we propose that many key players are active and interacting at different stages of disease progression. It is likely that future interventions will result from the combination of different drugs simultaneously targeting different molecules.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…While it is difficult to grasp and integrate the enormous number of published results, it is clear that NDO pathophysiology is complex and, consequently, its treatment and management is difficult. Like other researchers [ 18 ] and following the present review, we propose that many key players are active and interacting at different stages of disease progression. It is likely that future interventions will result from the combination of different drugs simultaneously targeting different molecules.…”
Section: Discussionsupporting
confidence: 67%
“…The fine molecular mechanisms involved in NDO emergence and maintenance are currently better understood [ 18 ], but remain challenging for clinicians and researchers. A fully effective treatment, able to revert urinary dysfunction, remains to be identified and there is ample need to improve symptomatic care for NDO patients and, as a consequence, their quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…After SCI, long-term dysuria and urine retention will lead to the hypertrophy of the bladder wall with a high ratio of collagen to muscle [ 30 , 31 ]. It was found that the thickness of the bladder wall after SCI was correlated with the recovery of bladder function, and that the mechanism might cause changes in altered c-fiber efferent activity [ 31 33 ] and the expression of some protein receptors [ 34 37 ]. Our electrophysiological assay has shown that SCDEs can promote the recovery of nerve conduction function after SCI by inhibiting inflammation, which may involve an improvement in the activity of C-afferent fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Rahnamai et al [ 37 ] reported the roles of prostaglandins and PDE in the development of proinflammatory OABs and suggested treatment with COX-2 inhibitors and PDE inhibitors for OABs. Accordingly, celecoxib was included in the present study as a reference treatment for OABs [ 38 , 39 ]. The inclusion of celecoxib in the experimental design also helped to consolidate the conclusion on the dual protective actions of vinpocetine on MetS-associated OABs via the anti-inflammation and preservation of cAMP in the detrusor muscles ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%